2010
DOI: 10.1111/j.1574-6968.2010.02162.x
|View full text |Cite
|
Sign up to set email alerts
|

HtpS, a novel immunogenic cell surface-exposed protein of Streptococcus suis, confers protection in mice

Abstract: Streptococcal histidine triad protein was identified recently as a cell surface-associated protein family. Five members of this family (PhtA, PhtB, PhtD, PhtE and HtpA), derived from Streptococcus pneumoniae and Streptococcus pyogenes, have been shown as antigens that confer protection to the host on infection. In this report, a gene sequence highly homologous to htpA and phtD (designated htpS, the histidine triad protein of Streptococcus suis) was identified from S. suis 2 Chinese strain 05ZYH33. Our data rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…In addition to six previously identified elements (capsular polysaccharides [CPS], 20 , 101 extracellular protein factor [EF], 102 fibronectin binding factor [FBP], 103 muramidase-released protein [MRP], 102 a protein of 38 kDa localized on bacterial surface [abbreviated 38 kDa], 104 and thio-activated hemolysin with known crystal structure [Suilysin, SLY]) 105 , 106 plus implication into bacterial meningitis, 107 11 more members have been supplemented into this group that include SspA, the surface-associated subtilisin-like serine protease, 41 , 108 , 109 HtpS, a novel immunogenic cell surface-exposed protein, 110 and Sat surface protein 111 , 112 (Table 2). Like FBP, 103 the gene SSU05_1311 with unknown function was determined to be one more surface anchored fibronectin-binding protein.…”
Section: Molecular Mechanism For Streptococcus Suis Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to six previously identified elements (capsular polysaccharides [CPS], 20 , 101 extracellular protein factor [EF], 102 fibronectin binding factor [FBP], 103 muramidase-released protein [MRP], 102 a protein of 38 kDa localized on bacterial surface [abbreviated 38 kDa], 104 and thio-activated hemolysin with known crystal structure [Suilysin, SLY]) 105 , 106 plus implication into bacterial meningitis, 107 11 more members have been supplemented into this group that include SspA, the surface-associated subtilisin-like serine protease, 41 , 108 , 109 HtpS, a novel immunogenic cell surface-exposed protein, 110 and Sat surface protein 111 , 112 (Table 2). Like FBP, 103 the gene SSU05_1311 with unknown function was determined to be one more surface anchored fibronectin-binding protein.…”
Section: Molecular Mechanism For Streptococcus Suis Infectionmentioning
confidence: 99%
“…In addition, HtpS, a putative member of histidine triad protein family, was determined to be cell surface-associated protein that was expressed during the infection of Chinese SS2 strain 05ZYH33 110 . Moreover, recombinant HtpS protein was demonstrated to function as a protective antigen against SS2 infections 110 . Similarly, Zhang et al 124 recently defined another new infection-associated antigen protein, Trag, using in vivo-induced antigen technology (IVIAT).…”
Section: Molecular Mechanism For Streptococcus Suis Infectionmentioning
confidence: 99%
“…Even though their individual physiological functions are not yet fully understood, their highly immunogenic character defines them as potential vaccine antigens [33], [34]. Indeed, administration of PhtA, PhtE or PhtD (also referred to as HtpS in Streptococcus suis ) protects mice against S. pneumoniae colonization of the nasopharynx and against bacteremia by inducing a humoral response [35], [36], [37]. In this context, PhtD appears especially attractive because it shows the uppermost efficacy of protection in nasopharyngeal colonization models and displays the highest level of conservation among S. pyogenes , S. agalactiae , S. suis and S. pneumoniae [37], [38], [39] as well as across pneumococcal serotypes [40], [41].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, administration of PhtA, PhtE or PhtD (also referred to as HtpS in Streptococcus suis ) protects mice against S. pneumoniae colonization of the nasopharynx and against bacteremia by inducing a humoral response [35], [36], [37]. In this context, PhtD appears especially attractive because it shows the uppermost efficacy of protection in nasopharyngeal colonization models and displays the highest level of conservation among S. pyogenes , S. agalactiae , S. suis and S. pneumoniae [37], [38], [39] as well as across pneumococcal serotypes [40], [41]. In addition, single phtD deletion in S. pneumoniae induces significant attenuation in intranasal challenge model [25] suggesting its involvement in the pathogenesis of pneumococcal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Adamou et al [19] found that although the sequence identity among four pht genes in S. pneumoniae varied from only 32% to 87%, a typical character of 4–6 duplicated histidine triad motifs was consistently shared by each protein. Searching for this signature, researchers subsequently identified genes homologous to pht genes in two other human pathogens, S. pyogenes [18], [22] and S. agalactiae [23]; and also in the zoonotic pathogen S. suis [24], [25]. The identified pht homologs were named, htp A and slr in S. pyogenes ; sht and blr in S. agalactiae ; and htpS in S. suis .…”
Section: Introductionmentioning
confidence: 99%